2021
DOI: 10.7554/elife.66694
|View full text |Cite
|
Sign up to set email alerts
|

A phase transition enhances the catalytic activity of SARM1, an NAD+ glycohydrolase involved in neurodegeneration

Abstract: Sterile alpha and toll/interleukin receptor (TIR) motif-containing protein 1 (SARM1) is a neuronally expressed NAD+ glycohydrolase whose activity is increased in response to stress. NAD+ depletion triggers axonal degeneration, which is a characteristic feature of neurological diseases. Notably, loss of SARM1 is protective in murine models of peripheral neuropathy and traumatic brain injury. Herein, we report that citrate induces a phase transition that enhances SARM1 activity by ~2000-fold. This phase transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 40 publications
3
41
1
Order By: Relevance
“…4C). Crowding agents also increase the activity of the TIR domain of human SARM1, as well as plant TIR domains [15,42], suggesting that the mechanism of TIR regulation is strongly conserved.…”
Section: The Nad + Glycohydrolase Activity Of Tir-1/sarm1 Is Activated By a Phase Transitionmentioning
confidence: 99%
See 4 more Smart Citations
“…4C). Crowding agents also increase the activity of the TIR domain of human SARM1, as well as plant TIR domains [15,42], suggesting that the mechanism of TIR regulation is strongly conserved.…”
Section: The Nad + Glycohydrolase Activity Of Tir-1/sarm1 Is Activated By a Phase Transitionmentioning
confidence: 99%
“…C. elegans carrying these same mutations, edited into the genome using CRISPR/Cas9, fail to induce p38 PMK phosphorylation, are unable to upregulate immune effector expression, and have enhanced susceptibility to bacterial infection. Importantly, we labeled the TIR-1/SARM1 protein with a fluorescent tag at its genomic locus and demonstrated for the first time that TIR-1/SARM1 oligomerizes into visible puncta within the intestine in response to physiologic stimuli, including both a pathogen and non-pathogen stress.In a contemporaneous study, Loring et al demonstrated that human SARM1 aggregates and undergoes a phase transition to potentiate its intrinsic NAD + glycohydrolase activity [15]. These authors studied SARM1 in the context of neuronal degeneration as it was previously demonstrated that loss of mammalian SARM1 protects against axonal degeneration following neuronal injury [16][17][18].…”
mentioning
confidence: 99%
See 3 more Smart Citations